The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27908
|View full text |Cite
|
Sign up to set email alerts
|

Board # 70 : Comparing the Effectiveness of Semester-long vs. Accelerated-summer Course Offerings

Abstract: Many of the foundational courses in undergraduate engineering programs are essential prerequisites for the core major-specific courses pertaining to the respective engineering degree, and hence typically have high enrollments. As a result, in addition to being offered during the regular semesters (Fall and Spring semesters, which are typically about 15 weeks in duration), many of these are also offered in an accelerated format over summer sessions (typically about 5 weeks in duration). Such a different manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Although this variable was present, the results were inconsistent with other studies that concluded a better performance in accelerated courses than in typical semester courses. 27 However, other studies reported an equivalent student performance between the two different terms. 28…”
Section: Achievement Of Learning Outcomesmentioning
confidence: 96%
“…Although this variable was present, the results were inconsistent with other studies that concluded a better performance in accelerated courses than in typical semester courses. 27 However, other studies reported an equivalent student performance between the two different terms. 28…”
Section: Achievement Of Learning Outcomesmentioning
confidence: 96%
“…At PUWL, Statics during the Summer semester comprises 35 total, 1-hour class sessions spread over a period of 8 weeks, rather than 42 class sessions over 16 weeks as offered in the Fall and Spring semesters. Although we have not studied students' comparative performance in Statics at PUWL, many studies in engineering mechanics [7] and in a variety of other disciplines [8], [9] have shown that students in accelerated and intensive Summer courses demonstrate academic outcomes that are proportional, or are even an improvement, when compared to similar students enrolled in traditional semester schedules. Researchers have tied these improvements to both the compressed timeline and the intensity of instruction in such courses [8], [10].…”
Section: Why Statics?mentioning
confidence: 99%